Metabolic Interaction Between Schwann Cells and Axons Under Physiological and Disease Conditions - Bouçanova, Filipa; Chrast, Roman (Frontiers in Cellular Neuroscience, 2020)
Recent research into axon-glial interactions in the nervous system have made a compelling case that Schwann cells (SC) have a relevant role in the metabolic support of axons, and that this role is independent from myelination itself. In this mini-review we summarize some of those observations, point out a few limitations and discuss the potential clinical relevance of this knowledge. First, we introduce SC, their development and main roles, and follow with an evolutionary perspective of their metabolic function. Then we provide evidence of the myelin-independent aspects of axonal support and of their coupling to neuronal metabolism. Finally, we address the opportunity to use SC-axon metabolic interactions as therapeutic targets to treat peripheral neuropathies.